Inserção comercial externa e doença holandesa no Brasil no período recente (2002-2008) - Silva, Michael Gonçalves da (2011)
The evidence for the hypothesis about the \"Dutch Disease\" was the theme in Brazil this dissertation. The appreciation of the exchange rate, high prices international commodities over the period 2002-2008 xare variables that increase the evidence for this hypothesis. Thus besides discuss the main theoretical contributions on the theme, the first chapter discusses the possibility of Dutch Disease in Brazil presenting the arguments against and in favor of its existence. A very brief discussion on the theories of trade was also presented in the opening chapter, because the hypothesis of \"Dutch Disease\" may be assessed as a problem of international trade. The second chapter included the examination of macroeconomic variables that are related to the \"Dutch Disease\" in the period 2002-2008: rate exchange, investment, production and export of agricultural commodities and mineral and industrial production. The third and final chapter aimed to aggregate data through the use of methodologies of Pavitt (1984), OECD and Lall (2000). After the data aggregation Results indicated that when considering only exports from Brazil between 2002-2008, the symptoms of \"Dutch Disease\" are not checked, ie not visible to the shrinkage of the industry in Brazil from exports. When considering the trade balance, the symptoms of \"disease Dutch \"are stronger, since the balances of commercial sectors intensive in natural resources are increasing (surplus) and decreasing industrial balances (deficit).